English For Academic Purposes (Eap) Learning Management With CLT Approach To Improve Quality Of Accounting Study Program Graduates Unpam And STEI – SEBI (Case Study on Accounting Management Study Program UNPAM and STEI-SEBI in South Tangerang and Bojongsari Depok) - Tutut Sumartini (CV. AFDIFAL MAJU BERKAH, 2022)
The demand of English language skills proficiency for university graduates now tends to communicate instead of mastering grammar or structure. The ability to discuss and understand about the field of work are very important in order to make them profesionals and have have high competitiveness. In general, this study aims to look at how the management of learning English EAP (English for Academic Purposes) in the accounting study program at Unpam and STIE-SEBI. Specifically this study aims to see how the planning, implementation, evaluation, obstacles encountered and support for facilities and infrastructure as well as learning outcomes. By using the principles and functions of management and supported by the CLT (Communicative Language Teaching) approach in learning English EAP, this research uses a descriptive method and a qualitative approach. While the research technique uses field observations, interviews, and document studies. The findings of this study generally indicate that EAP learning has been carried out even though it is not yet fully caused by several factors including: inadequate planning, implementation of learning that is not in accordance with the learning objectives which include teaching materials that are not in accordance with student needs, lecturer readiness, evaluation the lack of attention, lack of support for facilities and infrastructure for learning